Implementasi Sistem Informasi dalam Rangka Peningkatan Kinerja BKM BAGUS (Badan Keswadayaan Masyarakat Banaran Guyup Sejahtera) pada Desa Banaran Kecamatan Grogol Kabupaten Sukoharjo - Sri Hariyati Fitriasih, Andriani Kusumaningrum (STMIK Sinar Nusantara, 2011)
Many agencies in areas that are still using manually system in resolving a problem, especially in BKM GOOD still using manual methods. With the development of the age then the system will be changed manually by creating an application program that can be used to facilitate or assist the existing problems with computerization, especially in improving the performance of the BKM GOOD to be more effective and efficient. With the making of this application program is expected to improve performance in processing and storage in BKM GOOD as well as enhance the ability of their employees by implementing a new computerized system